How destination image and trust mediate e-WOM's impact on halal tourism intentions - Wibawa, Dian Prihardini; Yanto, Yanto; Zulkarnain, Ariandi (Faculty of Economics, Universitas Islam Indonesia, 2025)
Purpose – This study examines the mediating role of destination image and destination trust in the relationship between Electronic Word-of-Mouth (e-WOM) and the intention to visit halal tourism destinations, specifically focusing on Bangka Belitung. Methodology – This study employed a quantitative approach, collecting data from 292 respondents via an online survey. SEM was used to test the relationships among e-WOM, destination image, destination trust, and intention to visit. Validity and reliability tests, as well as goodness-of-fit measures, were applied to assess the model's robustness.Findings – The results indicate that e-WOM significantly influences both destination trust and destination image. However, neither destination image nor destination trust directly affect the intention to visit, and e-WOM itself does not have a direct significant impact on the intention. These findings suggest that, while e-WOM fosters positive perceptions and trust, other factors are more critical in driving the halal tourism intention.Implications – This study provides valuable insights for tourism stakeholders, particularly in halal tourism, by highlighting the importance of managing e-WOM to enhance trust and image. However, halal tourism providers must prioritize authenticity, cultural sensitivity, and visitor engagement to attract and retain tourists.Originality – This study contributes to the literature by exploring the mediating effects of destination image and trust in halal tourism, challenging the assumption that positive perceptions are always translated into behavioral intentions. It expands the understanding of how e-WOM impacts tourist decision making within a specific cultural and religious context.